ANALISA KINERJA RUAS PADA JEMBATAN MAHKOTA II KOTA SAMARINDA - BUDIANTO, ARIF SETYO (KURVA S JURNAL MAHASISWA, 2018)
he bridge is a construction structure that allows transportation routes through rivers, lakes, times, highways, railroads and others. As the population increases, the movement of transportation in the Mahkota II Bridge area increases and influences the segment performance and service level at the Mahkota II Bridge through the community to carry out daily activities to the destination through the Crown Bridge II section. The existence of the Mahkota II Bridge which is the connecting bridge of many activities to mobilize the movement of traffic flow must calculate the current capacity of the bridge to measure the performance and level of service for the Crown Bridge II section. Analysis carried out manually in accordance with the conditions of traffic flow in Indonesia. In this case an analysis was carried out using the 1997 Indonesian Road Capacity Manual (MKJI 1997) to take into account traffic performance. Traffic data obtained from a field survey conducted for 4 days is Monday, Wednesday, Saturday and Sunday, date (July 2, July 4, July 7 and July 8 2018) during rush hour which is presented in the form of a vehicle data table . Based on the results of the performance analysis on the Mahkota II Samarinda bridge using the MKJI 1997 method, the highest volume of Mahkota II Samarinda on Saturday is 1003.25 smp / hour with the highest Level Of Service (LOS) occurring on Saturday at 0.33, with a level service category "B".